Origin of the contact force-dependent response of triboelectric nanogenerators. (May 2021) - Min, Guanbo; Xu, Yang; Cochran, Peter; Gadegaard, Nikolaj; Mulvihill, Daniel M.; Dahiya, Ravinder
Abstract: Triboelectric nanogenerators (TENGs) have attracted significant interest as the alternative source of renewable energy. Their performance is believed to depend on the contact force, but its origin is yet to be established. Herein, we show that the origin lies in the real contact area A r, probed with novel experiments specifically designed for this purpose. The open circuit voltage V oc, short circuit current I sc and A r for a TENG, having two nominally flat tribo-contact surfaces, were found to increase with contact force/pressure. The A r is notably small at low pressures (0.25% at 16 kPa) that are typically experienced in wearable applications. However, it increases 328 fold to as much as 82% when it saturates beyond about 1.12 MPa pressure - achievable for impact with ocean waves. Critically, V oc and I sc saturate at the same contact pressure as A r suggesting that electrical output follows the evolution of the A r . Assuming that tribo-charges can only transfer across the interface at areas of real contact, it follows that an increasing A r with contact pressure should produce a corresponding increase in the electrical output. These results underline the importance of accounting for real contact area in TENG design to boost their performance, the distinction between real and nominal contact area in tribo-charge density definition, and the possibility of using TENGs as a self-powered pressure/load sensors. Crucially, the results indicate that the large contact pressures, readily available in applications such as road-tyre contact and wave energy, alone could be enough to boost the performance, thus avoiding the need for costly surface engineering to increase A r . Graphical Abstract: ga1 Highlights: Origin of the contact force-dependent performance of TENGs investigated. Real contact area & electrical output measured over wide contact force range. Origin is contact force-dependent real contact area owing to surface roughness. Major implications for definition & measurement of tribocharge density. Major implications in TENG design, pressure sensor design & high force applications.